Perancangan Website Promosi dan Pemesanan Sembako Rumah Tangga di Sampoerna Retail Community Annisa Deli Serdang dengan Menggunakan Metode Waterfall - Dinda Dwijayanti; Furqan Khalidy; Mardiah Mardiah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The rapid advancement of information technology has encouraged businesses to utilize websites as promotional and ordering media to improve service effectiveness. SRC Annisa Deli Serdang still conducts product promotion and ordering manually, resulting in limited marketing reach and inefficient data management. This study aims to design and develop a website for promoting and ordering household products to enhance operational efficiency and customer service quality. The research employed the Research and Development (R&D) method using the Waterfall development model, which consists of requirements analysis, system design, implementation, testing, and maintenance. Data were collected through observation, interviews, and literature review, while system functionality was evaluated using Black Box Testing. The results indicate that the developed website successfully provides integrated features, including product catalogs, online ordering, customer management, product management, and sales reporting. All system functions operated according to user requirements and performed effectively. Therefore, the developed website provides an effective solution for improving promotional activities, accelerating the ordering process, and supporting more efficient and integrated sales management.